Neonicotinoids stimulate H2-limited methane emission in Periplaneta americana through the regulation of gut bacterium community. (15th September 2021) - Bao, Haibo; Gao, Haoli; Zhang, Jianhua; Lu, Haiyan; Yu, Na; Shao, Xusheng; Zhang, Yixi; Jin, Wei; Li, Shuqing; Xu, Xiaoyong; Tian, Jiahua; Xu, Zhiping; et al.
Abstract: Methane emitted by insects is considered to be an important source of atmospheric methane. Here we report the stimulation of methane emission in the cockroach Periplaneta americana and termite Coptotermes chaohuensis, insects with abundant methanogens, by neonicotinoids, insecticides widely used to control insect pests. Cycloxaprid (CYC) and imidacloprid (IMI) caused foregut expansion in P. americana, and increased the methane emission. Antibiotics mostly eliminated the effects. In P. americana guts, hydrogen levels increased and pH values decreased, which could be significantly explained by the gut bacterium community change. The proportion of several bacterium genera increased in guts following CYC treatment, and two genera from four could generate hydrogen. Hydrogen is a central intermediate in methanogenesis. All increased methanogens in both foregut and hindgut used hydrogen as electron donor to produce methane. Besides, the up-regulation of mcrA, encoding the enzyme for the final step of methanogenesis suggested the enhanced methane production ability in present methanogens. In the termite, hydrogen levels in gut and methane emission also significantly increased after neonicotinoid treatment, which was similar to the results in P. americana . In summary, neonicotinoids changed bacterium community in P. americana gut to generate more hydrogen, which then stimulated gut methanogens to produce and emit more methane. The finding raised a new concern over neonicotinoid applications, and might be a potential environmental risk associated with atmospheric methane. Graphical abstract: Image 1 Highlights: F0B7 Stimulation of methane production in insects by neonicotinoid insecticides was first reported. F0B7 Neonicotinoid treatment changed bacterium community in gut to produce more hydrogen. F0B7 Methanogens in gut use higher hydrogen concentrations to generate and emit more methane. F0B7 It is a potential environmental risk concern with atmospheric methane of using neonicotinoids. Abstract : Neonicotinoids stimulate H2 -limited methane emission in methanogenic insects through the regulation of gut bacterium community, which raised a potential environmental risk.